К морфо-функциональному анализу крестовидных связок коленного сустава некоторых млекопитающих - Высоцкий, А.М. (Вестник зоологии, 1973)
It is established that in structure and function of cruciate ligaments of knee joint there are essential differences in plantigrade, digitigrade and unguligrade animals. Cruciate ligaments not only brake the flexing-extensing movements in the knee joint in the extreme phases, but also hinder the rotation movements, making the joint more stable.